KEDUDUKAN HUKUM PENGUSAHA REKANAN PEMERINTAH DENGAN BADAN USAHA JASA KONSTRUSI PEMBUAT SERTIFIKAT - Wida Farida (Journal of Law ( Jurnal Ilmu Hukum ), 2016)
ABSTRACT Wida Farida,  Legal notch entrepreuneur partners with the government  and business entiries of construction services tke certifies, supervised by Kunti Widayati, SH. M.Hum dan Syamsul Bahrie, SH.M.HumThis  study aims  to  determine  how the  application  of  business  entity certificate a requirement in the implementation of procurement auctions of construction tield in East Kalimantan;   for perpetration of guods and service providrs in  assessment process  granting formal recognition in computerized state level and the ability of Business enterprises in the field of construction service baed on  classification   and  qualification that are realized in the new of business entility certificate in the assement prosess capacity of business senterpris competency in the quafication and the ability of the business enterprise  in the feld of  contruction  services in to  business-level sevices competency.Based on the research conduend, of has been knom that the problems that   onse with tegard to the certification eatity are : 1.    The existence    of certification  of  business intitis in the tender prousess of government in the lity of   East Kalimantan    sometimes   overlovoked by the tender commite in the proses of  determmininy the urner to  the anesin to cntrasy to the pronsions of presidential beerce no. 54 of 2010 and Act No.18 of 1999 on Construction services . 2.       Factor that lead to defeets in govenmet projeet‟s anetin prosess in East Kalimantan  Are : a.    Limited     understanding    of    the  tender committee    of    the   provision   of govenement goods and services aictin. b.  The indivation of   intent   committed  by  the authin    comitte   caused by the presence of  gratification    collusion    between  the    entity and  tender committee.Contruction as the embodiment of the registration results, enther in the form of the individual if business entity keyword :  Business entity certificate.